I would die for you - Jones, Sandie (Minotaur Books, 2025)
"California, 2011: Nicole Forbes lives a quiet life in a small seaside Californian town with her husband and daughter. She is not expecting a writer to knock on her door asking for her personal insight into the downfall of the biggest British band of the 1980s - unveiling the threads of a life she put behind her years ago. The same day, her daughter goes missing and the school claims her aunt picked her up . . . but she doesn't have an aunt. Convinced of a link between the two, Nicole is forced to revisit long-abandoned memories from her past to protect everything she now holds dear. London, 1986: Sixteen-year-old Cassie is obsessed with the hottest band in London, Secret Oktober. Harboring an intense crush on the leading man, Ben Edwards, she will do anything she can to capture his attention among the throngs of groupies at the band's scandalous backstage parties. But when Ben discovers her older sister Nicole singing at a local bar one night, he can't help but feel drawn to her, setting in motion a collision course that could tear their family apart. Infused with the sounds of the 80s, this thrilling new novel from the inimitable Sandie Jones will captivate her readers, as she explores what the frenzy of fandom can lead to in this shocking blockbuster"--